2021
DOI: 10.3390/su131810398
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Safety Climate in Construction Projects between Workers and Managers/Supervisors in the Developing Country of Iran

Abstract: What are the different perceptions on safety climate (SC) by workers and managers/supervisors engaged in the construction industry of developing countries? Reconciling these two differing views is pivotal for mitigating and avoiding both the injured and fatal accidents in the construction industry, especially in those developing countries where safety conditions are poor and unpredictable, and safety measures are inadequate in most cases. To answer this research question, the collective perceptions of 118 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
(77 reference statements)
1
14
0
Order By: Relevance
“…Workers’ Safety Priority and Risk Non-Acceptance (Dim 5) (LC: M = 3.00, SD = 0.428; MNC: M = 2.95, SD = 0.433, p = 0.345). Our study results are supported the findings of a study conducted in Iran, as well as another in Hong Kong, which showed that the importance of co-workers in the SC of the construction industry is more important than in developed countries [ 40 ]. In this regard, our own findings revealed a significant difference in the mean scores between workers employed by LCs and MNCs.…”
Section: 0 Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Workers’ Safety Priority and Risk Non-Acceptance (Dim 5) (LC: M = 3.00, SD = 0.428; MNC: M = 2.95, SD = 0.433, p = 0.345). Our study results are supported the findings of a study conducted in Iran, as well as another in Hong Kong, which showed that the importance of co-workers in the SC of the construction industry is more important than in developed countries [ 40 ]. In this regard, our own findings revealed a significant difference in the mean scores between workers employed by LCs and MNCs.…”
Section: 0 Discussionsupporting
confidence: 91%
“…This highlights management’s reactive approach towards safety. According to Daniel et al [ 40 ] blame may be a barrier to learning, when accountability and criticism are dominant features of the work situation. Safety tends to be excessively managed through formal procedures as a means of self-preservation, thereby resulting in an increasingly prescriptive and inflexible compliance culture.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Before conducting EFA, however, we needed to perform a Bartlett's test to determine whether the sample was suitable for EFA (Chan et al, 2021 ). The Bartlett's test found that the correlations, when taken collectively, were significant at the 0.001 level.…”
Section: Resultsmentioning
confidence: 99%
“…The main contractor must reduce construction accidents and negative environmental impacts to comply with regulatory requirements and remain competitive [14,15]. The main body of the main contractor's safety behavior is the project management team, which consists of two parts, i.e., the old employees who are promoted from the grass-roots construction workers to the management and the university graduates with higher educational backgrounds [16].…”
Section: The Characteristics Of Safety Behaviors Of the Main Contract...mentioning
confidence: 99%